(untitled) (International Journal of Psychiatric Nursing, 2022)
Background: Substance Abuse is a phenomenon in the world and has invaded the human society as the most important social damage. Substance abuse is a nonadaptive model of drug use which results in advance problem and consequences , and includes a set of cognitive , behavioural , and psychological symptoms1. Methods: It was a Quasi Experimental study, total 60 substance abusers were selected ( 30 samples each for experimental and control group) by using convenient sampling technique. Structured questionnaire was used to collect the demographic characteristics & to assess the level of life skill practices of substance abusers residing in rehabilitation centre for both experimental and control group, followed by administration of Life skill training program for experimental group only. Results: The findings of the study revealed that difference between pre-test and post-test life skill score ‘t’ value was 14.57 for degree of (39) at 0.05 level of significance. This shows that there was significant increase in life skill practices of substance abusers after administration of Life skill training programme. The post-test mean life skill practice score of experimental group and post-test mean life skill practice score of control group shows ‘t’ value of 11.316 for the degree of freedom (78) at 0.05 level of significance. Conclusion: Human society has been challenged with Substance abuse and sustained notable ﬁnancial and spiritual losses. The problem of abuse is one of the topfour world crises and the main social crisis in India. The findings of study reveals that there was significant increase in life skill practices of experimental group than the control group after administration of Life skill training programme1.